2009
DOI: 10.1128/jvi.01402-09
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Specificity and Relative Clonal Abundance Do Not Affect CD8 Differentiation Patterns during Lymphocytic Choriomeningitis Virus Infection

Abstract: To evaluate the impact of immunodominance on CD8 T-cell properties, we compared the functional properties of dominant and subdominant populations in the response to lymphocytic choriomeningitis virus (LCMV). To improve functional discrimination, in addition to the usual tests of phenotype and function, we used a sensitive technique that allows the screening of all CD8 effector genes simultaneously in single cells. Surprisingly, these methods failed to reveal a major impact of clonal dominance in CD8 properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…PB1-F2 62 emerges relatively late in the response. Although not as striking as the influenza results presented in this study, the observation that naive CTLps do not exhibit synchronized proliferation to establish an acute-phase immunodominance hierarchy is supported by other studies that have analyzed the evolution of archetypal CTL immunodominance hierarchies to LCMV and Listeria monocytogenes (38)(39)(40). These studies showed that the relative magnitudes of epitopespecific CTL populations differed early, compared with at the peak of the established response.…”
Section: Discussionsupporting
confidence: 82%
“…PB1-F2 62 emerges relatively late in the response. Although not as striking as the influenza results presented in this study, the observation that naive CTLps do not exhibit synchronized proliferation to establish an acute-phase immunodominance hierarchy is supported by other studies that have analyzed the evolution of archetypal CTL immunodominance hierarchies to LCMV and Listeria monocytogenes (38)(39)(40). These studies showed that the relative magnitudes of epitopespecific CTL populations differed early, compared with at the peak of the established response.…”
Section: Discussionsupporting
confidence: 82%
“…4A), a slightly lower capacity to secrete cytokines in CD70 x−/− cells probably also contributed. It is also possible that some antigen-specific cells were unaccounted for due to TCR-downregulation (50). T-bet and Eomes, transcription factors that govern the CD8 T cell cytotoxic program, and the majority of surface markers of differentiation, such as CD122 (β component of IL-2 and IL-15 cytokine receptors), CD25 (β component of IL-2 receptor), and Ly6C, were indistinguishable between the strains at the peak of the response (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that CD8 T cells only produce these mediators when they are in direct contact with antigen-presenting cells in different tissues. However, in mice infected with either with LCMV 39 or Listeria monocytogenes, 30 tissue-resident CD8 T cells also rarely produced these mediators. Therefore, the contribution of CD8 T cells to the production of IL-2, TNF-␣, and the chemokine CCL3 during HIV infection remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%